2015
DOI: 10.1007/s11999-015-4504-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Predict Pain and Physical Health After Lower Extremity Trauma

Abstract: Background There has been increasing evidence to support the importance of psychosocial factors to poor outcomes after trauma. However, little is known about the contribution of pain catastrophizing and fear of movement to persistent pain and disability. Questions/purposes Therefore, we aimed to determine whether (1) high pain catastrophizing scores are independently associated with pain intensity or pain interference; (2) high fear of movement scores are independently associated with decreased physical health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 65 publications
5
51
0
4
Order By: Relevance
“…The Lower Extremity Assessment Project study first reported on the importance of low self‐efficacy (the patient's confidence in being able to resume life activities) to long‐term outcomes following traumatic lower‐extremity injury (Bosse et al, ), with more recent evidence supporting the association between self‐efficacy and pain at hospital discharge (Archer, Abraham, Song, & Obremskey, ). Archer et al and others have also found that patients who display pain catastrophizing behavior (tendency to focus on, ruminate, and magnify pain sensations) and/or fear of movement are at risk for more severe pain and disability up to 2 years after trauma (Archer, Abraham, & Obremskey, ; Archer, Abraham, et al, ; Nota et al, ; Vranceanu et al, ). Overall, studies suggest that psychosocial risk factors, especially those related to pain beliefs and behaviors, are potential targets for cognitive and behavioral strategies that address maladaptive beliefs and avoidance of activities (Vranceanu et al, ; Zale, Ring, & Vranceanu, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Lower Extremity Assessment Project study first reported on the importance of low self‐efficacy (the patient's confidence in being able to resume life activities) to long‐term outcomes following traumatic lower‐extremity injury (Bosse et al, ), with more recent evidence supporting the association between self‐efficacy and pain at hospital discharge (Archer, Abraham, Song, & Obremskey, ). Archer et al and others have also found that patients who display pain catastrophizing behavior (tendency to focus on, ruminate, and magnify pain sensations) and/or fear of movement are at risk for more severe pain and disability up to 2 years after trauma (Archer, Abraham, & Obremskey, ; Archer, Abraham, et al, ; Nota et al, ; Vranceanu et al, ). Overall, studies suggest that psychosocial risk factors, especially those related to pain beliefs and behaviors, are potential targets for cognitive and behavioral strategies that address maladaptive beliefs and avoidance of activities (Vranceanu et al, ; Zale, Ring, & Vranceanu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional data suggests post-injury anxiety, depression, posttraumatic stress symptoms, and pain catastrophizing predict pain persistence after acute injury [2; 31]. The developmental and interpersonal factors unique to childhood may limit the generalizability of these adult findings, making it critical to conduct similar prospective studies of youth with new-onset MSK pain.…”
Section: Introductionmentioning
confidence: 99%
“…Rumination causes a patient to perpetually dwell on the pain, magnification is an unhealthy focus and awareness of the pain and its potential side effects, and helplessness is feeling unable to do anything to reduce the intensity of the pain (Sullivan, ; Sullivan, Bishop, & Pivik, ). High levels of catastrophizing are associated with increased pain intensity (Archer et al, ; Das De, Vranceanu, & Ring, ; Edwards, Smith, Stonerock, & Haythornthwaite, ; Khan et al, ; Ozkan, Zale, Ring, & Vranceanu, ), pain interference (Archer et al, ; Leeuw, Goossens, et al, ), disability (Das De et al, ; Ozkan et al, ; Teunis, Bot, Thornton, & Ring, ), opioid use (Helmerhorst, Vranceanu, Vrahas, Smith, & Ring, ), and risk of developing chronic pain (Flaskerud, ; Khan et al, ).…”
Section: Multidimensional Psychosocial Screening Toolsmentioning
confidence: 99%
“…However, PTs across the U.S. have demonstrated significant inconsistency in identifying risk factors for chronic pain and disability (Beneciuk, Lentz, He, Wu, & George, ). Physical examination findings are the primary focus for most PTs, but research to date suggests that the most important prognostic factors are psychosocial in nature (Archer, Abraham, & Obremskey, ; Archer, Castillo, Wegener, Abraham, & Obremskey, ; Noehren et al, ; Piva, Fitzgerald, Wisniewski, & Delitto, ; Vargas‐Prada & Coggon, ). In‐fact, psychosocial factors have stronger associations with the transition from acute to chronic pain than any other factor (Foster & Delitto, ; Katz & Seltzer, ; Williams, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation